Tantularisme, Pluralitas Agama dan Toleransi (Studi Kasus Masyarakat Ketanggi-Ngawi) - Moh Toriqul Chaer (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2012)
The objectives of this article are: first, to discover the background of religious pluralism in Javanese society, notably among the communities in Ketanggi; second, to explore religious practices in Ketanggi; and third, to explore the religious attitudes of Ketanggi people towards religious pluralism. This article is based on field research carried out in Ketanggi sub-district of Ngawi, East Java, which is inhabited by the communities with different religious backgrounds. This paper argues that religious commitment among Ketanggi people is partly based on ‘tantularisme’, a sort of ethical principle which emerges as a result of the encounters between religion and local wisdom. The reception of Ketanggi people towards religious and cultural pluralism is partly expressed in the concept of lilo legowo (voluntary reception towards the other) which in turn become foundation of religious tolerance in that area. Keywords: religious pluralism, tantularism, and Javanese culture.